Leisure in pedagogical key: meanings of school leisure in public schools of Quindío, Colombia (Impetus, 2021)
Based on the several meanings attributed to the Leisure by the school actor’s, introducing progress made in the framework of the doctorate research called: “The leisure in key pedagogical”. Its design is taken from the complementarity ethnographic, allowing us reveal the meanings that encloses the entertainment for school culture in the educational context in Colombia, especially in the State of Quindío, and make a contrast from the practice, a theoretical approach on this complex concept and polysemous. Reveal the pedagogical keys of leisure at school would open a horizon of possibilities for an education of leisure as sense, alive and lived, individually and collective process. Prior to the analysis of results, it is necessary to present, by way of reflection, a theoretical approach on leisure in key humanist for going deeper then in theories of education of the leisure and, finally, provide some glances attributed to leisure from the voices of the participants in this research.